2020
DOI: 10.1111/1365-2656.13202
|View full text |Cite
|
Sign up to set email alerts
|

Stay home, stay safe—Site familiarity reduces predation risk in a large herbivore in two contrasting study sites

Abstract: 1. Restricting movements to familiar areas should increase individual fitness as it provides animals with information about the spatial distribution of resources and predation risk. While the benefits of familiarity for locating resources have been reported previously, the potential value of familiarity for predation avoidance has been accorded less attention. It has been suggested that familiarity should be beneficial for anti-predator behaviour when direct cues of predation risk are unclear and do not allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 65 publications
(107 reference statements)
2
39
0
Order By: Relevance
“…In our study area, there were no natural predators. However, in presence of predation risk the attraction to familiar areas could be related to an avoidance tactic 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study area, there were no natural predators. However, in presence of predation risk the attraction to familiar areas could be related to an avoidance tactic 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in large groups would increase their conspecific interactions and social bonding without the same scramble competition for resources. In particular, if a migrant loses a calf to predation during the previous summer, the security of the human refuge and social ties on the winter range may foster the shift in migratory tactic (Switzer, 1997;Hoover, 2003;Gehr et al, 2020).…”
Section: Implications For Maintaining Partial Migrationmentioning
confidence: 99%
“…Two main hypotheses have been formulated for the fitness benefits associated with site familiarity: (i) improved resource acquisition through the memorization of resource locations and attributes 10,15 , and (ii) predator avoidance through the knowledge of fine-scale variations in predation risk and of escape routes 46 . Previous work has shown that in roe deer, individuals rely on memory to efficiently track the spatio-temporal changes in food availability within their familiar environment 21 but are also prone to elevated predation risk from Eurasian lynx (Lynx lynx) when outside of their familiar space 47 . These two benefits of site familiarity are difficult to disentangle in nature; in our study, both factors may likely have driven the revisitation patterns that contributed to the emergence of roe deer home ranges.…”
Section: For a Cognitive Model Including Perception And Memory)mentioning
confidence: 99%